Trade Policies and The Export Performance of Indonesia, 1983-1997 - Agus Eko Nugroho (The Winners, 2001)
Article figures out trade policies and performance of Indonesia in 1983-1997 by presenting introduction, a brief review of international trade theory, the exchange rate policy, and trade promotion export-led performance. It is concluded that the government has promoted the export-increase of manufacturing exports in 1990.